Precipitation Process in Additively Manufactured Maraging 300 - Hermansson, Erik (My University, 2021)
The precipitation process of maraging 300 steel produced with Laser Powder Bed Fusion, (LPBF), was examined using atom probe tomography. To achieve this, samples were subjected to an aging heat treatment at 500 °C for 15 min, 30 min and 180 min, in addition a sample from the as-built block was also analysed. In the as-built condition initial precipitation of Ni3(Ti, Mo) was detected together with a clustering of nickel and titanium. When aged for 15 minutes the sample showed more developed Ni3(Ti, Mo)-spheres as well as Ni3(Mo, Ti)-rods. There was also very slight precipitation of the Fe7Mo6 μ-phase at points of intersection between these rods. Upon further aging the Ni3(Ti, Mo)-spheres generally decreased in size while the Ni3(Ti, Mo) formed larger precipitates of both plate- and rod-configuration. The μ-phase saw drastic increases in its size and number density upon aging for 180 minutes. It was still only found in connection with Ni3(Mo, Ti)-rods, indicating that it had formed from these. At the same time there was some new Ni3(Ti, Mo)-phase created as part of the Ni3(Mo, Ti)-rods. This is likely a consequence of the μ-phase attracting molybdenum from the rods. As this transfer of molybdenum could start diminishing the size of the rods and the rods were at their largest at 180 minutes, it is likely the rods that contribute the most to the strength of the steel, as the 3 hour aging time is the one suggested in the literature for optimum strength.
Keywords: maraging 300; APT; precipitate; additive manufacturing; LPBF; Maraging; Age-hardening; 18Ni300